2007
DOI: 10.1016/j.freeradbiomed.2007.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase mediates endotoxin-induced production of nitric oxide and cytotoxicity in murine macrophages

Abstract: Aldose reductase (AR) is a ubiquitously expressed protein with pleiotrophic roles as an efficient catalyst for the reduction of toxic lipid aldehydes and mediator of hyperglycemia, cytokine, and growth factor-induced redox-sensitive signals that cause secondary diabetic complications. Although AR inhibition has been shown to be protective against oxidative stress signals, the role of AR in regulating nitric oxide (NO) synthesis and NO-mediated apoptosis has not been elucidated to date. We therefore investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 73 publications
3
37
0
1
Order By: Relevance
“…Therefore, understanding the mechanism of RMG activation is a necessity for preventing these ocular diseases. Ramana and colleagues conducted many studies showing that AR plays a key role in modulating inflammatory responses in macrophages [3032]. In agreement with Ramana’s group, we previously demonstrated that either genetic ablation or pharmacological inhibition of AR attenuates endotoxin-induced inflammatory responses in macrophages and primary RMG [25, 26].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, understanding the mechanism of RMG activation is a necessity for preventing these ocular diseases. Ramana and colleagues conducted many studies showing that AR plays a key role in modulating inflammatory responses in macrophages [3032]. In agreement with Ramana’s group, we previously demonstrated that either genetic ablation or pharmacological inhibition of AR attenuates endotoxin-induced inflammatory responses in macrophages and primary RMG [25, 26].…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies also implicate AR in the pathogenesis of uveitis [2527] and fibrotic changes associated with posterior capsular opacification [28, 29]. Genetic or pharmacological blockade of AR successfully alleviates inflammatory responses induced by endotoxin [25, 26, 3032] or hyperglycemia [3335]. Our previous study showed that genetic or pharmacological downregulation of AR prevents endotoxin-induced inflammatory responses in RMG primary cell cultures [26].…”
Section: Introductionmentioning
confidence: 99%
“…This effect may not be peculiar to aldose reductase inhibitors but perhaps relative to the presence or absence of aldose reductase activity based on new studies using siRNA for aldose reductase. These studies show a diminished NO production and iNOS expression in LPS-treated macrophages [62].…”
Section: Limitationsmentioning
confidence: 64%
“…In this study, we also found that MEPA suppresses the Aktdependent activation of NF-κB, suggesting that MEPA affects the regulation of the inflammatory signal cascade. Nevertheless, further work is required to substantiate these observations in light of the study that revealed the role of the transcriptional factor AP-1 expression of proinflammatory genes [21].…”
Section: Discussionmentioning
confidence: 99%